2010
DOI: 10.1007/s11242-010-9606-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Pore-Scale Mechanisms of Carbonated Water Injection

Abstract: Carbon dioxide (CO 2 ) injection is a well-established method for increasing recovery from oil reservoirs. However, poor sweep efficiency has been reported in many CO 2 injection projects due to the high mobility contrast between CO 2 and oil and water. Various injection strategies including gravity stable, WAG and SWAG have been suggested and, to some extent, applied in the field to alleviate this problem. An alternative injection strategy is carbonated water injection (CWI). In CWI, CO 2 is delivered to a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 14 publications
1
77
0
Order By: Relevance
“…This is likely due to dissolved CO 2 in both phase of crude oil and brine that increases with pressure. Oil swelling is one of the most important mechanisms that have also been observed at carbonated water injection prior to the CO 2 injection in the micromodel tests using the light and heavy oils [5]. Under the same pressure, increase in IFT is expected due to the lower solubility of carbon dioxide in the brine and oil phases at higher temperature.…”
Section: Effect Of Pressure On the Carbonated Brine-crude Oil-co 2 Iftmentioning
confidence: 94%
See 3 more Smart Citations
“…This is likely due to dissolved CO 2 in both phase of crude oil and brine that increases with pressure. Oil swelling is one of the most important mechanisms that have also been observed at carbonated water injection prior to the CO 2 injection in the micromodel tests using the light and heavy oils [5]. Under the same pressure, increase in IFT is expected due to the lower solubility of carbon dioxide in the brine and oil phases at higher temperature.…”
Section: Effect Of Pressure On the Carbonated Brine-crude Oil-co 2 Iftmentioning
confidence: 94%
“…Moreover, they observed that CO 2 flooding performances after WI and CWI are different. That was, the injection of carbon dioxide after CWI recovered more oil compared to that after WI [5,38]. The proposed mechanism for the higher performance of CO 2 I in the former process was due to the existence of a continuous oil film between the water and the displacing CO 2 phases.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…e most commonly used methods for EOR by CO 2 injection are CO 2 -water alternate flooding, immiscible flooding, miscible flooding, and cyclic CO 2 injection [5,6]. e mechanism of EOR by injecting CO 2 primarily includes a reduction in the viscosity of crude oil and expansion, vaporization, extraction, and improvement in the oil removal efficiency [7,8].…”
Section: Introductionmentioning
confidence: 99%